Embryo Transfer in Subfertile Mares - Katila, T. (Acta Vet Scand, 1989)
Four subfertile mares (at least 2 barren years) were used as donors in an embryo transfer program. The embryo recovery rate was 50%, varying between 0-100. The transfer of 9 embryos resulted in the pregnancy rate of 44%. The efficiency of embryo transfer using subfertile mares is low. In this material 20% of flushings resulted in a pregnancy.